The yak - A valuable genetic resource of alpine region - PRASAD, S K (The Indian Journal of Animal Sciences, 2013)
Yak, the ship of cold region, serves the need for milk, meat, fibre and as a pack animal of the mountainous regions of China, Mongolia, Tajakistan, zbekistan, Russia, India, Nepal and Bhutan. It is adapted to higher altitude of 2 000 to 5 000 m above MSL and can withstand freezing temperature of -50oC and low oxygen tension. Nature has endowed yak with all the necessary anatomical and physiological manifestations to withstand the rough and harsh conditions of cold mountain. ous regions. Immunogenetic studies carried out to investigate the chara teristics of yak erythrocyte antigens revealed the presence of A2, Y, X2, J and Z antigens in high proportion. Twenty-nine bovine red cell antigens were detected on yak erythrocytes. Yak has 30 pairs of chromosomes, of which 29 pairs are autosomes which are acrocentric. The Y chromosome is submetacentric.